Strengthening the Character of Environmental Care Based on Local Wisdom in Coastal Communities - Mariatul Kiptiah; Nurul Huda (FKIP, Universitas Palangka Raya, 2024)
Environmental care character is an attitude and action to prevent damage to the surrounding natural environment, and develop efforts to repair natural damage that has occurred. Local wisdom is part of cultural values that live in the minds of most people, so it is believed and always guides behavior. The purpose of this research is to analyze the form of strengthening the character of environmental care based on local wisdom in coastal communities. This research uses a qualitative approach, with descriptive research methods. The results of this study concluded that strengthening the character of environmental care based on local wisdom in coastal communities is an innovation in developing community attitudes, skills, and knowledge about the environment.